Crypto‐giving and surveillance philanthropy: Exploring the trade‐offs in blockchain innovation for nonprofits. Issue 4 (23rd December 2020) - Howson, Peter
Abstract: A blockchain is a smart electronic database, distributed to all users, immutably tracking every transaction that has ever taken place between nodes on a network. The technology is being used by some nonprofits to address various operational challenges, including attaching automated conditions to charitable donations facilitated by programmable "crypto‐giving" platforms. Drawing from analysis of technical documents provided by active crypto‐giving projects, this review considers how these platforms enable radical shifts in sectoral power relations through "surveillance philanthropy". This algorithmic surveillance ensures project funding fully reflects the interests of donors, while potentially restricting nonprofits in meeting the dynamic and complex needs of project beneficiaries. The paper considers the benefit trade‐offs from crypto‐giving platforms in three areas of utilization: (a) new forms of donor engagement and fundraising, (b) new tools for organizational governance, and (c) novel provision of development assistance. Despite the possible efficiency and transparency benefits of crypto‐giving platforms, more research and practitioner engagement is required to ensure the sector's funding is secure and sustainable, without entailing significant risks for proposed beneficiaries.